Identifying weaknesses and strengths of existing I4.0 Readiness Indices to enhance INDI 4.0 - Hasbullah Hasbullah; Salleh Ahmad Bareduan (SINERGI, 2024)
Indonesia has low Industry 4.0 (I4.0) readiness in ASEAN and has the INDI 4.0 Instrument (Indonesia Industry 4.0 Readiness Index), which is less comprehensive and accurate. An Initial survey confirmed that only 56.86% of respondents agreed that INDI 4.0 accurately measures readiness in the manufacturing industry. Unlike primary I4.0 indices, INDI 4.0 lacks comprehensive Industry 4.0 dimensions and characteristics, as many literature and other indices cover. This study aims to identify weaknesses and strengths of major I4.0 indices by comparing them to enhance INDI 4.0. This paper identified gaps in existing major I4.0 indices by scoping review method. However, each index contributes to increasing practicality, fulfilling latent needs, and expanding complementary perspectives in measuring readiness and adoption of I4.0 based on studies, viewpoints, uniqueness, and views of each. This study offered a more comprehensive perspective, especially from developing countries like Indonesia, with industries struggling to adopt I4.0 to fill loopholes in existing major indices that are generally from developed countries, so most companies in their study have advanced or implemented I4.0 and are too focused and too oriented on technology. The findings from this paper are expected to contribute to industry, practitioners, and academicians in increasing accuracy when measuring readiness toward adopting I4.0.